Different Clinical Presentations of Pulmonary Embolism: A Case Series - Santhosh K B; Rakesh Nayaka K; Rahul S R (National Board of Examinations Journal of Medical Sciences)
Pulmonary embolism can present with a wide spectrum of clinical symptoms ranging from asymptomatic to life threatening phase to emergency department. It is one of the medical challenges with respect to its diagnosis and treatment. We present a case series of five such cases of presented to a tertiary care centre Subbaiah Institute of Medical Sciences and Research Centre, Shivamogga, Karnataka, India. Clinical, electrocardiographic and point of care ultrasound of heart, lungs and bilateral lower limb two point compression ultrasound done at the bedside along with all the initial stabilization steps done and their outcome are described in this case series. Early high degree of clinical suspicion and appropriate treatment is crucial. Failing which can lead to mortality. This case series highlights the different clinical presentations of pulmonary embolism including periarrest states that can present to emergency departments.